Pengaruh Lembar Kerja Siswa IPA Terpadu Tema Gelombang dalam Kehidupan Mengintegrasikan Keterampilan Literasi Terhadap Kompetensi Siswa Kelas VIII SMPN 8 Padang - Nurhafizah Nurhafizah; Asrizal Asrizal; Ramli Ramli (PILLAR OF PHYSICS EDUCATION, 2018)
Literacy skills required students to answer the challenges of the 21st century. The Government of Indonesia seeks to meet those needs through the School Literacy Movement. School literacy movement is applied through the growing interest rates of reading, responding to enrichment books, and reading strategies in all subjects. In addition, the government also tries to improve students' competence through integrated science learning in junior high school. The reality in the field shows that the learning outcomes of integrated science are still low and the students' literacy is still limited to reading ability only. An alternative solution to solving this problem is to apply integrated sciencestudent worksheet integrate literacy skills. The purpose of this research is to investigate the effect of the application of the Integrated Science Student Worksheet on the theme of waves in life integrating literacy skills to the competence of grade VIII students SMPN 8 Padang. The type of research used is quasi experiment with research design that is non control research design equivalent only with postes. The sampling technique used is purposive sampling and random cluster sampling. Instruments for collecting data consist of written test sheets for knowledge competencies and observation sheets for skills competencies. Research data were analyzed by statistical analysis using normality test and homogeneity test and equality test of two averages. Based on the data analysis can be stated that the application of integrated LKS wave theme in life integrate literacy skills in scientific approach give a meaningful influence to the competence of students of class VIII SMPN 8 Padang. Integrated the integrated science student worksheet gives influence to students' competence on knowledge, skill, and attitude aspects at 95% level of trust. Thus it can be stated that integrated science student worksheet integrated wave themes in effective life for use in integrated science learning.